Comparing patrons' renewal behavior before and after implementing more permissive loan rules. Issue 4 (1st October 2016) - Irwin, Ken
ABSTRACT: This article reports on a study of how long library patrons at 28 college and university libraries kept books checked out before and after a policy change allowing for longer circulation periods and more renewals. The behavior of most patrons remained similar before and after the policy change, with only a slight (7–14 day) lengthening of the length of circulation for many patrons. A significant minority of patrons made more extensive use of the longer loan periods, demonstrating the usefulness of the policy change for many users.